Bioinspired calcium phosphate composites - Wong, Emily Kai Lin (Nanyang Technological University, 2022)
Nacre-like composites, especially the ones with self-healing properties have attracted attention for their remarkable properties. To potentially replicate the structure and properties of bioinspired self-healing structural composites, we have fabricated self-healing gelatin-based hydrogels and calcium phosphate (CaP) bricks. Physical crosslinking (hydrogen and hydrophobic interactions) between gelatin and tannic acid (TA) demonstrates the self-healing and bioadhesive properties; that act as the interfacial soft layers of mortar. Cap such as hydroxyapatite is a major inorganic mineral, commonly found in our bones to facilitate bone reconstruction will be used to fabricate as bricks. However, the adhesiveness between the gelatin-TA hydrogel and CaP has never been studied. We tested the shear bond strength between gelatin-TA hydrogel and CaP via shear lap test and found it to be between 21.37 ± 4.2 kPa and 40.4 ± 9.0 kPa. According to our optical microscope and shear lap test results, we found that the mechanical properties of our gelatin-based hydrogel could be tuned by the TA concentration. The development of self-healing gelatin-based hydrogels that have strong bonding to CaPs will allow the construction of CaP composites with brick-and-mortar structures for biomedical applications.